PRIMARY SCHOOL STUDENTS IN RURAL INDONESIA CONSTRUCTED IN A PHOTO: SOCIAL JUSTICE, EQUITY, AND ACCESS TO EDUCATION - Sutaryo, Sutaryo (EDUKASI, 2021)
The purpose of this paper is to examine how primary schools students in rural Indonesia are constructed in a photo. The paper discusses issues on social justice, equity, and access to education for primary school students in rural Indonesia as visually represented in the photo. Thematic analysis is used within the context of critical approach by referring to relevant literatures. Why the photo as an interesting primary source for qualitative research is selected and why the thematic analysis and the critical approach are applied in this paper are briefly described.